The effect of orthodontic treatment with and without tooth extraction on stomatognathic function: Pengaruh perawatan ortodonti dengan dan tanpa pencabutan gigi terhadap fungsi stomatognatik - Mansjur Nasir; Eka Erwansyah; Susilowati (Makassar Dental Journal PDGI Makassar, 2023)
Extraction commonly used in orthodontic treatment with crowding teeth. However, the total functional effect caused by extrac-tion and orthodontic treatment remains unclear. This study is aimed to explain the effect of orthodontic treatment with and with-out extraction procedures on dental morphology and masticatory function. The study was conducted using a cross-sectional study design, consisting of pre- and post-treatment groups (25 cases of extraction and 22 cases of non-extraction); and the long-itudinal study consisted of 23 extraction cases and 3 non-extraction cases. Morphological and functional recording was carried out with several assessments, including irregularity index values, masticatory efficiency, number of occlusal contacts, and EMG analysis. Cross sectional, irregularity index showed a significant decrease in malocclusion (p<0.005). There was no significant change in masticatory efficiency. The occlusal contacts of extraction cases (A and C) tend to increase. The activity of the tem-poral (T) muscle was greater than that of the masseter (M) on EMG analysis. Almost all the results from the longitudinal stu-dies support the results from the cross-sectional studies. Results showed functional data immediately after extraction and amidst dynamic treatment decreased with occlusion instability. Both extraction and non-extraction cases improved morphologically and functionally after orthodontic treatment. It can be concluded that extraction of 4 premolars is not always associated with a negative impact on stomatognathic function when proper orthodontic treatment is performed after extraction.